A conceptual framework for the sustainability assessment procedures of the shrimp aquaculture industry in coastal Bangladesh. (8th March 2006) - Chowdhury, Md. Arif; Shivakoti, Ganesh P.; Salequzzaman, Md.
Shrimp aquaculture is now establishing itself as an important aquaculture industry in coastal Bangladesh. However, the benefit of this industry is concentrated to only the interests of a specific group of people who contribute a significant amount of foreign earnings to the nation, while the present development process is posing a challenge to the coastal sustainability, as well as the industry itself. This paper analyses the contexts of sustainability in relation to the coastal shrimp aquaculture industry and identifies the relevant sustainable factors or indicators for coastal Bangladesh. In addition, this paper examines these sustainability indicators quantitatively in regard to how they can be used through a unifying index that allows the present shrimp aquaculture to be assessed considering all sustainability components, such as environmental, economic and socio-cultural factors separately and in interaction with each other. Finally, this paper presents a conceptual framework for a sustainability assessment methodology of coastal shrimp aquaculture in Bangladesh.